Does changing from mercury to electronic blood pressure measurement influence recorded blood pressure? An observational study. - McManus, R; Mant, J; Hull, MR; Hobbs, F (2003)
Mercury sphygmomanometers have been commonly used in primary care to measure blood pressure but are associated with bias. Electronic blood pressure machines are being introduced in many practices and have anecdotally been associated with higher recorded blood pressure. This study examined recorded blood pressure in four practices before and after electronic blood pressure machine introduction. No consistent change in mean blood pressure was apparent following their introduction, but there was a large and significant fall in terminal digit preference suggesting improved precision of recording.